Tree Species Diversity Suppresses Soil Carbon Priming Effects in a Subtropical Forest - Pengpeng Duan; Xinyi Yang; Andrew T. Nottingham; Chaoqun Wang; Luiz A. Domeignoz‐Horta; Wolfgang Wanek; Xinli Chen; Yuqi Zhou; Hongzhao Yuan; Hu Du; Kelin Wang; Dejun Li (Ecology Letters, 2026)
Nature‐based climate solutions rely on the assumption that restoring plant diversity enhances soil organic carbon (SOC) sequestration. However, the persistence of SOC is threatened by the positive priming effects, where fresh plant carbon inputs accelerate the decomposition of native SOC. It remains unclear how increasing plant diversity impacts the soil priming effects. Here, using a natural tree species diversity gradient in a subtropical forest, we show that higher tree diversity was strongly associated with suppressed soil priming effects, attributable to reduced mineral protection of SOC and alleviated microbial energy limitation. Microbial community consequently shifts toward fast‐growing specialists that outcompete decomposers of chemically complex carbon. Our study reveals that tree species diversity is a key regulator of SOC persistence and demonstrates that the biodiversity‐driven priming suppression should be explicitly incorporated into nature‐based climate solutions and Earth system models to reduce critical uncertainties in carbon cycle projections.